2018
DOI: 10.1159/000494649
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Analysis of the Relationship Between RAS and RAF Mutations and MSI Status of Colorectal Cancer in Northeastern China

Abstract: Background/Aims: Colorectal cancer (CRC) is mainly caused by chromosomal instability (CIN) and microsatellite instability (MSI). The RAS and RAF genes are essential components of the CIN pathway, and several studies have found that RAS and RAF mutations are associated with MSI status in CRC. Here, we examined these three factors in CRC in Northeast China and aimed to reveal new details of the relationship between these mutations and MSI status. Methods: This study involved 290 patients with CRC who had RAS or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 29 publications
2
5
0
Order By: Relevance
“…This study demonstrates that RAS and KRAS mutant status underline special clinicopathological and molecular features. As reported in some studies [15,28,29], in our context, RAS mutated CC was associated with female gender, distal colon, classical adenocarcinoma subtype, moderately differentiated tumors, and presence of vascular invasion. Interestingly, our study demonstrated that CC with RAS and epically KRAS mutations show a lower rate of the total lymph node.…”
Section: Discussionsupporting
confidence: 85%
“…This study demonstrates that RAS and KRAS mutant status underline special clinicopathological and molecular features. As reported in some studies [15,28,29], in our context, RAS mutated CC was associated with female gender, distal colon, classical adenocarcinoma subtype, moderately differentiated tumors, and presence of vascular invasion. Interestingly, our study demonstrated that CC with RAS and epically KRAS mutations show a lower rate of the total lymph node.…”
Section: Discussionsupporting
confidence: 85%
“…Some scholars have found that it is more common in women, 20 which is consistent with our results, but there are also literatures showing that there is no significant difference between men and women. 21 In addition, we found that the T stage of dMMR CRC is late, and the degree of tumor invasion is deep, consistent with the conclusions of other scholars. 22 Our research also showed that compared with patients with pMMR CRC, dMMR patients had a larger maximum tumor diameter and a higher percentage of tumors over 5 cm.…”
Section: Clinicopathological Characteristics Of Patients With Dmmrsupporting
confidence: 89%
“…This is in the mid-range of reports from international series as shown in Table 4, where the proportion of RASmt was reported to range from less than 40% 12 up to 59%. 13 In our analyses, early data for both TRACC and TTT shows a RASmt rate around 40% and later data a RASmt rate around 50% in both databases. This increase largely coincides with the gradual uptake of extended RAS testing over several years, with further data on implication of RAS status on treatment, as well as easier access to EGFRi.…”
Section: Kras Mutation Only 470 (90%) E366 Discussionmentioning
confidence: 51%
“…The overall RASmt rate in our study of TRACC patients was 47% and for TTT was 45%. This is in the mid‐range of reports from international series as shown in Table 4, where the proportion of RASmt was reported to range from less than 40% 12 up to 59% 13 …”
Section: Discussionmentioning
confidence: 72%